The estrous stimulation of based on melatonin and progesterone during the non-breeding season in sheep - Saat, N.; Pancarci, S.; Risvanli, A. (Wiley, 2017)
[Abstract Not Available]
21st Annual Conference of the European-Society-for-Domestic-Animal-Reproduction (ESDAR) -- AUG 24-26, 2017 -- Bern, SWITZERLAND